Clinical outcomes of living donor liver transplantation for patients 65 years old or older with preserved performance status. Issue 4 (April 2014) - Ikegami, Toru; Bekki, Yuki; Imai, Daisuke; Yoshizumi, Tomoharu; Ninomiya, Mizuki; Hayashi, Hiromitsu; Yamashita, Yo‐Ichi; Uchiyama, Hideaki; Shirabe, Ken; Maehara, Yoshihiko
<x xml:space="preserve">Abstract</x> The purpose of this study was to determine the outcomes of living donor liver transplantation (LDLT) for elderly recipients. We reviewed 411 adult‐to‐adult LDLT cases, including 46 recipients who were 65 years old or older and 365 recipients who were less than 65 years old. The elderly group had a higher proportion of females (P = 0.04) and a smaller body surface area (P < 0.001) and more frequently underwent transplantation because of hepatitis C (P < 0.001) or hepatocellular carcinoma (P < 0.001). Elderly patients had less advanced liver disease with lower Model for End‐Stage Liver Disease (MELD) scores (P = 0.02) and preserved health without the need for prolonged hospitalization (P < 0.01). The transplanted graft volume/standard liver volume ratios were similar for the 2 groups (P = 0.22). The elderly group had fewer episodes of acute rejection (P = 0.03) but had more neuropsychiatric complications (P = 0.01). The 5‐ and 10‐year graft survival rates were comparable for the elderly group (89.8% and 77.8%, respectively) and the younger group (79.4% and 72.9%, respectively; P = 0.21). Seven recipients were 70 years old or older, and they had a mean MELD score of 15.6 ± 5.2; 6 of these patients were treated as outpatients before LDLT. All were alive after LDLT and showed good compliance with medical management with a mean follow‐up of 5.7 ± 3.0 years. In conclusion, LDLT can be safely performed and has acceptable long‐term outcomes for low‐risk elderly recipients with preserved performance status. Liver Transpl 20:408–415, 2014. © 2014 AASLD.